Literacies in early childhood : changing views, challenging practice - Makin, Laurie; Jones-Diaz, Criss (MacLennan + Petty, 2002)
The importance of literacy learning in the first years of school has long been recognised, but literacy experiences in the pre-school years have not always received sufficient attention. In Literacies in Early Childhood: Changing Views, Challenging Practice the authors redress this imbalance, with a focus spanning from birth to eight years. 'Literacy as social practice' is an overriding theme, and it is continually acknowledged that young children's understandings about literacy occur within their cultural and linguistic communities.